PHP and MySQL for dynamic web sites video quickstart guide - Ullman, Larry E. (Larry Edward), 1972-; Ullman, Larry E. (Larry Edward), 1972-; Safari eBooks ([S.l.] : Peachpit Press, 2011)
"It hasn't taken Web developers long to discover that when it comes to creating dynamic, database-driven Web sites, MySQL and PHP provide a winning open-source combination ... This guide is indispensable for beginning to intermediate level Web designers who want to replace their static sites with something dynamic."--Resource description page.
Title and imprint from resource description page (viewed Nov. 22, 2011).
This video tutorial is a companion to Larry Ullman's book PHP and MySQL for dynamic web sites, 4th ed., 2011.
Presenter, Larry Ullman.
Keywords: Web site development; Web sites -- Design; PHP (Computer program language); MySQL (Electronic resource); Electronic books